Legal Certainty For An Object That Is A Fiduciary Guarantee Which Has Not Been Removed After The Debt Is Removed - Utami, Fitri Pujianti; Darmadi, Nanang Sri; Mashdurohatun, Anis (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The relationship between creditors and debtors in the business world requires legal certainty, which is realized through collateral instruments, one of which is fiduciary collateral. Although Law No. 42 of 1999 concerning Fiduciary Collateral and Government Regulation No. 21 of 2015 stipulate the obligation to write off debts after debt repayment, practice shows that many collateral items are not written off, so the object remains listed as collateral. TypeThis research is normative juridical, using a conceptual juridical approach. The data used include primary, secondary, and non-legal data by collecting data through literature and analyzing it using prescriptive analysis to describe and evaluate the implementation of fiduciary roya. The procedure for the removal (roya) of fiduciary collateral is carried out by the creditor after the debtor has fully paid their obligations by submitting an application to the Fiduciary Registration Office, which then issues a Roya Certificate. However, because the removal is not automatic, differences often arise between the material and administrative removal of fiduciary collateral. This situation creates legal uncertainty, where the debtor cannot reuse the collateral, new creditors lose certainty, and potentially give rise to disputes. The roya mechanism in the Fiduciary Collateral Law needs to be strengthened with clear derivative regulations regarding time limits and sanctions for creditors who fail to comply, to prevent re-fiduciary collateral and provide legal certainty. System improvements can also be achieved through digitization and data integration between institutions, mandatory verification by notaries, and strengthening fiduciary certificates as executorial titles to more effectively protect creditors and debtors.